Highlighting the Proteasome: Using Fluorescence to Visualize Proteasome Activity and Distribution - Gan, Jin; Leestemaker, Yves; Sapmaz, Aysegul; Ovaa, Huib (Frontiers in Molecular Biosciences, 2019)
Proteasomes are critical proteases in the cell responsible for the turnover of many cytoplasmic and nuclear proteins. They are essential for many cellular processes and various diseases are associated with their malfunctioning. Proteasome activity depends on the nature of the catalytic subunits, as well as the interaction with associated proteasome regulators. Here we describe various fluorescence-based methods to study proteasome function, highlighting the use of activity-based probes to study proteasome localization, dynamics, and activity in living cells.